2020
DOI: 10.1112/jlms.12403
|View full text |Cite
|
Sign up to set email alerts
|

On the monoidal center of Deligne's category Re̲p(St)

Abstract: We explicitly compute a monoidal subcategory of the monoidal center of Deligne's interpolation category normalRe̲pfalse(Stfalse), for t not necessarily a natural number, and we show that this subcategory is a ribbon category. For t=n, a natural number, there exists a functor onto the braided monoidal category of modules over the Drinfeld double of Sn which is essentially surjective and full. Hence the new ribbon categories interpolate the categories of crossed modules over the symmetric groups. As an applicati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(23 citation statements)
references
References 25 publications
2
21
0
Order By: Relevance
“…The categories Z(Rep S t ), for t generic, and Z(Rep ab S d ), for d ∈ Z ≥0 , are infinite analogues of modular categories. This interpretation follows from [FL21,Theorem 3.27] where Z(Rep S t ) was shown to be a ribbon category and Section 3.8 where we prove that Z(Rep S t ) and Z(Rep ab S d ) are non-degenerate braided tensor categories. We note that these categories are also factorizable braided tensor categories by [EGNO15,Proposition 8.6.3].…”
Section: Introductionmentioning
confidence: 55%
See 4 more Smart Citations
“…The categories Z(Rep S t ), for t generic, and Z(Rep ab S d ), for d ∈ Z ≥0 , are infinite analogues of modular categories. This interpretation follows from [FL21,Theorem 3.27] where Z(Rep S t ) was shown to be a ribbon category and Section 3.8 where we prove that Z(Rep S t ) and Z(Rep ab S d ) are non-degenerate braided tensor categories. We note that these categories are also factorizable braided tensor categories by [EGNO15,Proposition 8.6.3].…”
Section: Introductionmentioning
confidence: 55%
“…In [FL21], the first and third listed authors started the investigation of Z(Rep S t ), showed that the latter is a ribbon category, and obtained invariants of framed links as an application. It was shown that the braided categories Z(Rep S t ) interpolate the braided categories Z(Rep S d ) in the sense that Z(Rep S d ) is the semisimplification of Z(Rep S d ) for d ∈ Z ≥0 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations